Augmenter of Liver Regeneration Protects Renal Tubular Epithelial Cells From Ischemia-Reperfusion Injury by Promoting PINK1/Parkin-Mediated Mitophagy - Zhu, Dong-Ju; Liao, Xiao-Hui; Huang, Wen-Qi; Sun, Hang; Zhang, Ling; Liu, Qi (Frontiers in Physiology, 2020)
Ischemia–reperfusion (I/R) is the most common cause of acute kidney injury (AKI) and can induce apoptosis in renal epithelial tubule cells. Mitochondrial dysfunction is one of the main reasons for I/R-induced apoptosis. Accumulating evidence suggests that PINK1/Parkin-mediated mitophagy possibly plays a renoprotective role in kidney disease by removing impaired mitochondria and preserving a healthy population of mitochondria. Our previous study showed that augmenter of liver regeneration (ALR) alleviates tubular epithelial cells apoptosis in rats with AKI, although the specific mechanism remains unclear. In this study, we investigated the role of ALR in I/R-induced mitochondrial pathway of apoptosis. We knocked down ALR with short hairpin RNA lentiviral and established an I/R model in human kidney proximal tubular (HK-2) cells in vitro. We observed that the knockdown of ALR aggravated mitochondrial dysfunction and increased the mitochondrial reactive oxygen species (ROS) levels, leading to an increase in cell apoptosis via inhibition of mitophagy. We also found that the PINK1/Parkin pathway was activated by I/R via confocal microscopy and Western blot. Furthermore, the knockdown of ALR suppressed the activation of PINK1 and Parkin. These findings collectively indicate that ALR may protect HK-2 cells from I/R injury by promoting mitophagy, and the mechanism by which ALR regulates mitophagy seems to be related to PINK1 and Parkin. Consequently, ALR may be used as a potential therapeutic agent for AKI in the future.